Clinicopathologic Characteristics of Gallbladder Adenomyomas and the Contribution of Macroscopic Sampling in Adenomyoma Diagnosis - Selma ŞENGIZ ERHAN; Sevinç HALLAÇ KESER; Mehmet ÖZER (Federation of Turkish Pathology Societies, 2020)
Objective: Adenomyoma, a reactive and hamartomatous lesion of the gallbladder, is included in the differential diagnosis of several benign and malignant lesions. Macroscopic sampling is very important in the determination of these lesions. The agreed macroscopy protocol in recent years has been prepared by the Hepatopancreatobiliary Pathology Working Group. We aimed to evaluate the clinicopathologic properties of adenomyoma cases in the gallbladder and the contribution of new macroscopy techniques to the diagnosis of adenomyoma in the pre-protocol and post-protocol parts of a one-year period. Material and Method: Two institutes were included in the study. Adenomyoma cases diagnosed in the pre-protocol and post-protocol periods of one year duration were included in the study. Slides and demographic properties of the cases were reexamined. Results: While adenomyoma was present in 22 of 1879 gallbladder before the protocol, it was observed in 32 of 1781 gallbladders in the post-protocol period. 17 of the cases were male and 37 were female. The mean age of the cases was 51.8. 52% of the lesions were located in the fundus. A gallstone was observed in 37 cases, and cholesterolosis in 14 cases. In the comparison of the two periods, the number of cases was lower in the post-protocol period but a 0.6% increase in the diagnosis of adenomyoma was found. Conclusion: Adenomyoma is one of the lesions of the gallbladder that should be recognized but can be easily overlooked macroscopically. When we conducted the sampling according to the last protocol, the increase in the diagnosis of adenomyoma showed that adequate and accurate sampling was very useful for the detection of adenomyoma in the gallbladder.